الطفل الجزائري، بين إكراهات الواقع وتطلعات الرؤية المستقبلية في كتابات - بن الحركات,الجمعي (University of Eloued جامعة الوادي, 2024)
لقد اضطلع الأديب "سعد مردف" بإنجاز مشروع أدبي منصب أساسا على رسم الطفولة الجزائرية في جزئياتها، وتفاصيلها، وكلياتها من خلال تبني استراتيجية واعية في الكتابة، تقوم على مهارة بارعة في توظيف سهل للآليات الفنية، والجمالية الهامة، من لغة، وأسلوب، وصور، وإيقاعات، وتشكيلات مختلفة، موازاة مع رؤيته الفكرية المحكمة، التي أثْرت بنجاح، وببراعة عوالم الدوال، والجماليات، والتشكيلات الفنية. Abstract: Saad Mredef has undertaken a literary project focused mainly on drawing the Algerian childhood in its particles, details and faculties through the adoption of a conscious strategy in writing based on a distinctive skill in employing all the important technical and aesthetic mechanisms, including language, style, image, rhythms and various formations, in parallel with the tight intellectual vision that successfully and brilliantly framed the worlds of signification, aesthetics and artistic formations.
سعد مردف
Keywords: سعد مردف; سيكولوجية الطفل; قيم الهوية; Saad Mredef; Children literature; child psychology; educational chant; Values of identity